ALL THAT WE ARE: PHILOSOPHICAL ANTHROPOLOGY AND ECOPHILOSOPHY. - Peterson, Keith R. (Cosmos & History, 2010)
Ecophilosophers have long argued that addressing the environmental crisis not only demands reassessing the ethical aspects of human and nature relations, but also prevailing theories of human nature. Philosophical anthropology has historically taken this as its calling, and its resources may be profitably utilized in the context of ecophilosophy. Distinguishing between conservative and emancipatory naturalism leads to a critical discussion of the Cartesian culture/nature dualism. Marjorie Grene is discussed as a resource in the tradition of philosophical anthropology which enables us to avoid dualistic thinking and espouse an emancipatory naturalism by resisting reductionism and acknowledging the diffuse dependence of human being on natural processes. In order to fully explicate the conditions of human dependence upon nature it becomes necessary to define an appropriate approach to ontology. This critical ontology facilitates a stratified understanding of the place of humans in nature without lapsing into reductivism or post-Kantian constructivism. It provides a sounder basis than either alternative for motivating a many- sided ecophilosophical perspective on human being.